Positron annihilation study of the vacancy clusters in ODS Fe–14Cr alloys. Issue 11 (13th April 2017) - Domínguez-Reyes, R.; Auger, M. A.; Monge, M. A.; Pareja, R.
Abstract: Oxide dispersion strengthened Fe14Cr and Fe14CrWTi alloys produced by mechanical alloying and hot isostatic pressing were subjected to isochronal annealing up to 1400 °C, and the evolution and thermal stability of the vacancy-type defects were investigated by positron annihilation spectroscopy (PAS). The results were compared to those from a non-oxide dispersion strengthened Fe14Cr alloy produced by following the same powder metallurgy route. The long lifetime component of the PAS revealed the existence of tridimensional vacancy clusters, or nanovoids, in all these alloys. Two recovery stages are found in the oxide dispersion strengthened alloys irrespective of the starting conditions of the samples. The first one starting at T > 750 °C is attributed to thermal shrinkage of large vacancy clusters, or voids. A strong increase in the intensity of the long lifetime after annealing at temperatures in the 800–1050 °C range indicates the development of new vacancy clusters. These defects appear to be unstable above 1050 °C, but some of them remain at temperatures as high as 1400 °C, at least for 90 min.